CHARACTER BUILDING AND CREATIVITY IN EARLY CHILDHOOD THROUGH TOTAL PHYSICAL RESPONSE WARM UP GAME - Ririn Ambarini (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study was aimed at determining the improvement of the character building and creativity levels of the students through TPR Warm Up Game. The study was action research including the activities of planning, implementation, data collection, and data analysis. The study was conducted in the second semester of the school year 2011/2012. The subjects were teachers and students of Class A of Doa Ibu kindergarten. Data were collected through observation, field notes, interviews, and documentation. The validity of the data was verified by triangulation. The data were analyzed using the descriptive qualitative flow model. Results show that there was an improvement in the character building and creativity levels of students after the implementation of the TPR Warm up Game. Improvement was also indicated by creative reactions, longer attention spans, self-confidence/organization, the expression of ideas, development of imagination, and increament of new vocabulary. The success of character building and creativity improvement is also supported by the methods of giving the opportunities for exploration and giving motivation in the form of praises